(3caGjI GdbfhY aj GdYed HGdQHY GdebWhYs
(3ChdgG (B:s
(3HYO GdHSedI hGdMeO dI agPg QSGdI eNJUQI aj GdYed HGdQHY GdTeGdj GdebhY GNJUQJgG ef QSGdJj GdeSeGI EXgGQ GdSQ GdehOY s
(3BNQgG (B:s
(3GdHGH GdNGeS YTQ aj eYQaI GdeGVj hGdHGbj ef Gddjd ai LgI GdchGcH s
(3Vef eLehY , JQJjHgG (B: 8s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3JHUQGJ GdCUd (B:s
Keywords: (3eJaQbGJs